Inovasi Keperawatan Tehnik Refleksi Pada Kasus Gastritis Dengan Pendekatan Teori Keperawatan Virginia Henderson Di Puskesmas Bermani Ulu - Wilianti, Astika; Handayani, Tita Septi; Aprianti, Delta (Universitas Dehasen Bengkulu, 2025)
Gastritis or commonly known as ulcers is a disease that often occurs in society, but this disease is often underestimated and underestimated by sufferers. Gastritis can cause a variety of symptoms, but the main symptom that ulcer patients often complain about is pain or discomfort that is blocked in the upper stomach. Foot Reflexology Technique Therapy or often called reflexology is massage therapy by applying pressure to nerve points on the feet or hands to provide bioelectric stimulation to certain body organs which can provide a feeling of relaxation and freshness because the blood flow in the body becomes smooth. The general aim of this case study is to apply Virginia Henderson's theory of treating ulcer patients by performing and teaching Reflexology Techniques to reduce pain intensity. This research was also conducted to find out whether Virginia Henderson's theory can be applied to ulcer patients by providing Reflexology Technique therapy.This case study method is a qualitative method with a case study research research strategy. The type of case study when carrying out caregiving is a research case study by applying Reflection Techniques through Virginia Henderson's surgical theory model to patients suffering from ulcer disease.Results of Bandage Care for Gastritis patients by applying Foot Massage Reflexology Technique Therapy using Virginia Henderson's Freezing theory is carried out using the Freezing process starting from assessing 14 providing basic human needs, Observing and Determining Problems, Freezing Actions, Freezing Implementation and Freezing Evaluation. The scheduled intervention is directed at helping to reduce pain intensity with Reflexology Technique therapy through the Virginia Henderson approach.Virginia Henderson's theory of the murder model can be applied and applied well in murders focused on ulcer cases. The suggestion for health workers is that reflexology technique therapy for patients suffering from rheumatism reduces the intensity of pain so that it can reduce activity disruption due to uncontrolled pain.